Karakteristik perkembangan fisik, kognitif, dan bahasa anak usia infant - Hikmawati, Aziza Ayu (Maliki Interdisciplinary Journal, 2023)
Children communicate using language with words that have unique meanings to convey their needs, thoughts, and feelings. However, they have limitations in understanding language from other people's perspectives because their understanding of language is limited to their own views. Children's language development is influenced by the development of symbolic functions, which greatly affect their ability to understand other people's points of view and improve problem-solving skills. Children have unique physical and psychological development characteristics. Therefore, it is important for teachers to design learning according to the characteristics of children and focus on their needs. School-age children need optimal physical and psychological development in aspects such as cognitive, language, physical-motor, social-emotional, and art. Thus, the design of language learning must be adapted to the child's level of development in order to avoid failure and frustration. A child-centered learning approach provides an opportunity for them to achieve success, but teachers still need to adjust learning activities so that they remain challenging according to the child's developmental level. Especially for young children, the cognitive aspect is the main focus where they learn to understand and deal with new tasks. Therefore, the mother's role in monitoring various aspects of child development, such as motor, sensory, physical, language, and emotional, is very important.